An Effective Double Verification-Based Method for Certifying Information Safety in Cloud Computing - Amanullah, M.; Mishra, Ved Prakash; Mayavan, L.; Tannady, Hendy; Kulkarni, Nandini; Kolandaisamy, Raenu (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Cloud computing is an architectural concept that offers computation and storage space as a service as well as on-demand, dynamic access to any type of service over the Internet. Storage as a service is one of the major services offered. Data are stored and managed at a cloud provider’s data centre using cloud computing services, which are entirely internet-based technology. Traditional cryptographic security based on the assumed difficulty of computer operations is facing tremendous challenges as a result of the evolution of information technology. The key concerns with cloud servers are successful safe communication and protecting sensitive data from unauthorized access on public networks. This protocol can be implemented using the exclusive-OR operation in traditional cryptography. Data security issues and supporting data security architecture are the key targets of this investigation. In the same way that it chooses a server for data storage that is quick, efficient, and light on resources, the system is made to prepare security procedures regardless of the order in which the data is stored. Cuckoo Search Algorithm (CSA) has been used to determine which available server is most suitable for a given task in wake-sleep distributed computing. Homomorphic encryption, where information is encrypted before being delivered to the server, is typically used to guarantee the veracity of the data being transmitted. To save on server resources and data storage, we’ve encrypted everything with ECDSA on the cloud server. It strengthens protections for user data in the cloud. At the end of the day, the system proves that data is secure, reliable, and private. Despite some drawbacks, this framework does provide safe methods of exchanging keys and backing up data, both of which are crucial for protecting the confidentiality of sensitive data kept in the cloud.